EFISIENSI KINERJA SASI TERIPANG PASIR (Holothuria scabra) DESA TUNGU KEPULAUAN ARU - Yona A. Lewerissa; Frederik W. Ayal; Yohana N. Letsoin (Universitas Pattimura, 2023)
The sandfish sea cucumber, Holothuria scabra, has economic value and is considered expensive, making it a target for utilization. The sandfish sea cucumber is found in the village of Tungu, but with the implementation of sasi (a traditional system of resource management), it is expected to ensure the sustainability of the sandfish sea cucumber resources. In reality, every time the sasi period is lifted, sandfish sea cucumbers are harvested without any size limitations and there are illegal captures by fishermen from outside the Aru Islands using complete diving equipment. Given these conditions, it is suspected that the sandfish sea cucumber population may decline. Therefore, this research was conducted in August-September 2018, with the aim of assessing the performance efficiency of the sasi system for sandfish sea cucumbers in Tungu Village. Data collection was done through observation and interviews with intentionally selected respondents and analyzed descriptively using several indicators. The research results showed that the catch of sandfish sea cucumbers amounted to 2,240 kg of dried weight, with varying selling prices according to size. The analysis of performance efficiency indicated that the sasi system for sandfish sea cucumbers in Tungu Village falls into the moderate category.